Continuous measurement of cerebral oxygen saturation (rSO 2) for assessment of cardiovascular status during hemorrhagic shock in a swine model - Navarro, Lais Helena Camacho [UNESP]; Lima, Rodrigo M. [UNESP]; Khan, Muzna; Dominguez, Wendy G.; Voigt, Richard B.; Kinsky, Michael P.; Mileski, William J.; Kramer, George C. (Wolters Kluwer, 2012)
Background: Early trauma care is dependent on subjective assessments and sporadic vital sign assessments. We hypothesized that near-infrared spectroscopy-measured cerebral oxygenation (regional oxygen saturation [rSO 2]) would provide a tool to detect cardiovascular compromise during active hemorrhage. We compared rSO 2 with invasively measured mixed venous oxygen saturation (SvO2), mean arterial pressure (MAP), cardiac output, heart rate, and calculated pulse pressure. Methods: Six propofol-anesthetized instrumented swine were subjected to a fixed-rate hemorrhage until cardiovascular collapse. rSO 2 was monitored with noninvasively measured cerebral oximetry; SvO2 was measured with a fiber optic pulmonary arterial catheter. As an assessment of the time responsiveness of each variable, we recorded minutes from start of the hemorrhage for each variable achieving a 5%, 10%, 15%, and 20% change compared with baseline. Results: Mean time to cardiovascular collapse was 35 minutes ± 11 minutes (54 ± 17% total blood volume). Cerebral rSO 2 began a steady decline at an average MAP of 78 mm Hg ± 17 mm Hg, well above the expected autoregulatory threshold of cerebral blood flow. The 5%, 10%, and 15% decreases in rSO 2 during hemorrhage occurred at a similar times to SvO2, but rSO 2 lagged 6 minutes behind the equivalent percentage decreases in MAP. There was a higher correlation between rSO 2 versus MAP (R =0.72) than SvO2 versus MAP (R =0.55). Conclusions: Near-infrared spectroscopy- measured rSO 2 provided reproducible decreases during hemorrhage that were similar in time course to invasively measured cardiac output and SvO2 but delayed 5 to 9 minutes compared with MAP and pulse pressure. rSO 2 may provide an earlier warning of worsening hemorrhagic shock for prompt interventions in patients with trauma when continuous arterial BP measurements are unavailable. © 2012 Lippincott Williams & Wilkins.
Keywords: cerebral oxygenation; Hemorrhage; near-infrared spectroscopy; trauma; propofol; animal experiment; animal model; artery catheter; blood pressure; blood sampling; blood volume; brain blood flow; cardiovascular function; conference paper; controlled study; female; fiber optics; heart output; heart rate; hemorrhagic shock; mean arterial pressure; near infrared spectroscopy; nonhuman; oximetry; oxygen saturation; priority journal; pulse pressure; regional oxygen saturation; venous oxygen tension; Animals; Brain; Brain Chemistry; Cardiac Output; Cardiovascular System; Cerebrovascular Circulation; Female; Monitoring, Physiologic; Oximetry; Oxygen; Shock, Hemorrhagic; Spectroscopy, Near-Infrared; Swine